2012
DOI: 10.1177/1010539512444776
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Hearing Loss and Associated Factors Among Vector Control Workers in a Malaysian State

Abstract: This study aims to determine the prevalence and associated factors of noise-induced hearing loss (NIHL) among vector control workers in the state of Negeri Sembilan, Malaysia. This was an analytical cross-sectional study conducted on 181 vector control workers who were working in district health offices in a state in Malaysia. Data were collected using a self-administered questionnaire and audiometry. Prevalence of NIHL was 26% among this group of workers. NIHL was significantly associated with the age-group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
7
1
1
Order By: Relevance
“…NIHL was not significantly associated with age, which was consistent with the outcome reported in a study among commercial fishermen . However, another study from Malaysia showed a different pattern, which reported that the NIHL was significantly associated with the age group of 40 years and above . Further studies are necessary to identify if age is an independent risk factor of NIHL after offsetting age‐related hearing loss through the adjustment of age .…”
Section: Discussionsupporting
confidence: 84%
“…NIHL was not significantly associated with age, which was consistent with the outcome reported in a study among commercial fishermen . However, another study from Malaysia showed a different pattern, which reported that the NIHL was significantly associated with the age group of 40 years and above . Further studies are necessary to identify if age is an independent risk factor of NIHL after offsetting age‐related hearing loss through the adjustment of age .…”
Section: Discussionsupporting
confidence: 84%
“…However, further analysis need to be done to fully understand about the relationships between them. Prevalence of hearing loss (73.3%) for manufacturing workers in this study was considered high compared to other local studies of different industries such as 57.0% in quarry workers (Filza Ismail et al 2013), vector control workers 26.0% (Masilamani et al 2014). When compared to the hearing loss prevalence of workers in other countries, the prevalence of respondents in this study showed a more severe condition as it was higher.…”
Section: Discussioncontrasting
confidence: 54%
“…A cross-sectional analysis showing a temporal problem might astrict the evidence for a causal relationship between occupational noise and unhealthy condition. However, the causal association between noise exposure and hearing abnormality has been acknowledged 34,35 . The variable of duration to occupation noise was based on own oral-report which could have led to bias, as workers may not have remembered clearly or could have potentially given false information about longer exposure time.…”
Section: Discussionmentioning
confidence: 99%